2017
DOI: 10.1080/01904167.2017.1384007
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced phosphorus fertilizers (Carbond P® and Avail®) supplied to maize in hydroponics

Abstract: Phosphorus (P) is poorly soluble in soil and has poor plant uptake efficiency. AVAIL Ò and Carbond P (CBP) are fertilizers that increase P-use efficiency (PUE) and yields on P limiting soils. The objectives of this study were to determine if mode of action for these products is related to physiological response, and to evaluate possible toxicity. AVAIL and CBP were compared to ammonium polyphosphate (APP) at pH 6 or 8 for hydroponically grown maize (Zea mays L.). Not surprisingly, biomass and P concentration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…If the crop did not respond to P, it can be concluded that it would be unlikely to respond to a P fertilizer enhancer (Hopkins, 2015;Summerhays et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…If the crop did not respond to P, it can be concluded that it would be unlikely to respond to a P fertilizer enhancer (Hopkins, 2015;Summerhays et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…We see evidence of this with other chemicals, such as with organic acids (Hopkins, 2015;Tan, 2014). This bond would have to be strong enough to prevent reaction with soil cations and yet be able to release the P at the root surface and/or internally.…”
Section: Mode Of Actionmentioning
confidence: 98%
See 3 more Smart Citations